Production of a Rich Fertilizer Base for Plants from Waste Organic Residues by Microbial Formulation Technology - Vurukonda, Sai Shiva Krishna Prasad; Fotopoulos, Vasileios; Saeid, Agnieszka (My University, 2024)
This review explores different methods of sustainably introducing nutrients from agro-industrial waste into the soil. The focus is on sustainable agriculture and how the soil system can be modified by introducing secondary raw materials and beneficial microorganisms. Soil is a nexus between plants and microorganisms that must be balanced. The article emphasizes the importance of maintaining the microbiological balance when supplying nutrients. This review is focused on the possible techniques involved in the production of biofertilizers and their mode of application into the soil system and on plants. We addressed several advantages concerning the use of beneficial microorganisms in waste management by microbial formulation techniques. Not only the advantages but several limitations and challenges were also discussed in regard to the large scale production of microbial products. Therefore, the proper treatment of industrial waste is essential so that we can preserve the environment and human safety and also achieve sustainable agriculture.
Keywords: waste processing; bioformulation; nutrient loop; soil microorganisms; sustainable agriculture